COMT val158met polymorphism and neural pain processing - Schmahl, Christian; Greffrath, Wolfgang; Rietschel, Marcella; Bohus, Martin (PLOS ONE, 2012)
A functional polymorphism (val158met) of the gene coding for Catechol-O-methyltransferase (COM) has been demonstrated to be related to processing of emotional stimuli. Also, this polymorphism has been found to be associated with pain regulation in healthy subjects. Therefore, we investigated a possible influence of this polymorphism on pain processing in healthy persons as well as in subjects with markedly reduced pain sensitivity in the context of Borderline Personality Disorder (BPD). Fifty females (25 patients with BPD and 25 healthy control participants) were included in this study. Genotype had a significant - though moderate - effect on pain sensitivity, but only in healthies. The number of val alleles was correlated with the BOLD response in several pain-processing brain regions, including dorsolateral prefrontal cortex, posterior parietal cortex, lateral globus pallidus, anterior and posterior insula. Within the subgroup of healthy participants, the number of val alleles was positively correlated with the BOLD response in posterior parietal, posterior cingulate, and dorsolateral prefrontal cortex. BPD patients revealed a positive correlation between the number of val alleles and BOLD signal in anterior and posterior insula. Thus, our data show that the val158met polymorphism in the COMT gene contributes significantly to inter-individual differences in neural pain processing: in healthy people, this polymorphism was more related to cognitive aspects of pain processing, whereas BPD patients with reduced pain sensitivity showed an association with activity in brain regions related to affective pain processing.
Gesehen am 04.04.2018